Blood antioxidant status of Stercorarius maccormicki and Stercorarius antarcticus from Potter Peninsula, 25 de Mayo (King George) Island, Antarctica - Di Fonzo, Carla Ianina; Montalti, Diego; Ansaldo, Martin (Polar Biology)
Oxidative stress is considered the main physiological mechanism involved in short- and long-term life histories, operating through the progressive deterioration of tissues, with consequences in the reproductive performance, growth patterns, aging, and survival. Besides, the Antarctic Peninsula environmental change, registered in the last decades, makes essential the antioxidant status knowledge of fauna and flora to optimize current management plans to protect Antarctic wildlife. Therefore, the present study aimed to investigate the differences between the oxidant-antioxidant status in adults and chicks´ blood of the skuas Stercorarius antarcticus and Stercorarius maccormicki. Through spectrophotometric techniques, the enzyme activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione S-transferase (GST) as well as the level of total glutathione (TG), total protein (TP), lipid peroxidation (LPO), and protein oxidation (PO) were measured. The adults of both species showed higher TG levels than the chicks. S. antarcticus adults were characterized by showing high GST activity and the highest total protein (TP) levels. Instead, S. maccormicki adults showed high levels of oxidative damage (PO and LPO) and high CAT activity. On the other hand, the chicks of both species were typified by the augmented SOD activity compared to those registered in adults. In turn, S. maccormicki chicks had increased GPx activity. Considering the multiple factors that affect the antioxidant status of both skua species, the information reported, herein, is a first promising dataset that would allow giving reference values for them. Fil: Di Fonzo, Carla Ianina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Montalti, Diego. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina. Consejo Nacional de Investigaciones ...